Land snails and slugs of Bau limestone hills, Sarawak (Malaysia, Borneo), with the descriptions of13 new species - Mohammad Effendi, Marzuki; Liew, Thor Seng; Mohd Azlan, Jayasilan (2021)
"is study presents a list of land snails and slugs found on limestone hills in the District of Bau, the state of Sarawak in Malaysian Borneo. Systematic and random sampling for land snails was conducted at eight limestone outcrops, namely, Gunung Stulang, Padang Pan, Gunung Kapor, Gunung Lobang Angin, Gunung Doya, Gunung Batu, Bukit Sekunyit and Gunung Sebayat. A total of 122 land snail species was documented with photographs of each species. Of the 122 species collected, 13 are new to science, namely, Acmella bauensissp. nov., Japonia bauensissp. nov., Plectostoma margaretchanaesp. nov., Micro-cystina arabiisp. nov., Microcystina atonisp. nov., Microcystina paripari sp. nov., Microcystina liratasp. nov., Microcystina oswaldbrakenisp. nov., Microcystina kilatsp. nov., Philalanka jambusanensissp. nov., Everettia microrhytidasp. nov., Everettia minutasp. nov., and Paralaoma sarawakensissp. nov.